2006
DOI: 10.1590/s0102-37722006000200003
|View full text |Cite
|
Sign up to set email alerts
|

Variáveis no ensino de discriminação para bebês

Abstract: RESUMO-A investigação das condições necessárias para aprendizagem de discriminações condicionais por bebês é um desafio devido às dificuldades relacionadas à manutenção de crianças pequenas em situações experimentais. O objetivo foi ensinar tarefas de pareamento de identidade para um bebê de 12 meses em um experimento conduzido na sala de uma creche. Brinquedos utilizados como estímulos eram expostos em um aparato constituído por três janelas recortadas em uma caixa diante das quais se sentava um experimentado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
19

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(32 citation statements)
references
References 7 publications
1
12
0
19
Order By: Relevance
“…It is also in play that children perform the role of speaker and modify the behavior of others, as well as benefit from instructions given by others and improve their listening skills. Considering the importance of teaching in play contexts, some studies were conducted with procedures similar to the play context and produced effective results regarding the efficacy of learning in this context (Gil et al, 2006;Sousa, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also in play that children perform the role of speaker and modify the behavior of others, as well as benefit from instructions given by others and improve their listening skills. Considering the importance of teaching in play contexts, some studies were conducted with procedures similar to the play context and produced effective results regarding the efficacy of learning in this context (Gil et al, 2006;Sousa, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have analyzed the role of the adult in proposing appropriate teaching conditions (Cruvinel, 2010;Gil, Oliveira, Sousa, & Faleiros, 2006;Greer & Ross, 2008;LeBlanc et al, 2009;Sousa, Souza, & Gil, 2013), planning the teaching so that the child is exposed to the stimulus for a determined number of times (Antoniazzi, Domeniconi, & Schmidt, 2014;Gurteen, Horne, & Erjavec 2011;Sousa et al, 2013) and also as a provider of the conditions subsequent to the response(s) that are reinforcers (Gil, Oliveira, & McIlvane, 2011;Sousa, Garcia, & Gil, 2014). In the study reported here, the adult that proposes appropriate teaching conditions is represented by the researcher, who adopted a favorable method for the study and, simultaneously, needed to consider the requirements of the target population, since they were children at risk of social vulnerability.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Especifi camente em relação à população de bebês, algumas das principais difi culdades relatadas nas pesquisas sobre equivalência podem ser somadas às difi culdades enfrentadas para a realização de outras investigações experimentais com bebês (Gil & Oliveira, 2003;Gil, Oliveira, Sousa & Faleiros, 2006;Pilgrim, Jackson & Galizio, 2000;Wilkinson & McIlvane, 2001).…”
Section: T P Oliveira E M S C a Gilunclassified
“…A literatura tem ressaltado que os resultados ainda são incipientes a respeito dos parâmetros necessários para investigar tais fenômenos na referida população (Gil & Oliveira, 2003;Gil, Oliveira, Sousa & Faleiros, 2006;O'Donnell & Saunders, 2003;Pilgrim, Jackson & Galizio, 2000;Wilkinson & McIlvane, 2001).…”
Section: Discussão Geralunclassified